1982
DOI: 10.1113/jphysiol.1982.sp014220
|View full text |Cite
|
Sign up to set email alerts
|

An ionophoretic study of the responses of rat caudal trigeminal nucleus neurones to non‐noxious mechanical sensory stimuli.

Abstract: SUMMARY1. Extracellular recordings of the responses of single caudal trigeminal nucleus neurones to non-noxious and noxious facial stimuli and to ionophoretically applied L-glutamate, L-aspartate and acetylcholine were made in urethane anaesthetized rats.2. Neurones excited by non-noxious mechanical stimuli were located primarily in the magnocellular part of nucleus caudalis, whereas neurones excited by both noxious and non-noxious stimuli were located either ventromedially to the magnocellular part ofnucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 36 publications
2
16
0
2
Order By: Relevance
“…Similarly we found no evidence for NMA receptor involvement in non-nociceptive responses of dorsal horn neurones. This result is consistent with results obtained in trigeminal dorsal horn with D-aminoadipate (Hill & Salt, 1982). There is, however, evidence that NMA antagonists can reduce the responses of spinal neurones to low-intensity mechanical (Davies & Dray, 1979) and electrical (Davies & Watkins, 1979, 1983Lodge et al 1983) activation of primary afferents.…”
Section: Dorsal Hornsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly we found no evidence for NMA receptor involvement in non-nociceptive responses of dorsal horn neurones. This result is consistent with results obtained in trigeminal dorsal horn with D-aminoadipate (Hill & Salt, 1982). There is, however, evidence that NMA antagonists can reduce the responses of spinal neurones to low-intensity mechanical (Davies & Dray, 1979) and electrical (Davies & Watkins, 1979, 1983Lodge et al 1983) activation of primary afferents.…”
Section: Dorsal Hornsupporting
confidence: 85%
“…The non-selective amino acid antagonist cis-2,3-piperidine dicarboxylate (PDA) 184 N-METH YLASPARTATE AND SPINAL SENSORY RESPONSES 185 was less effective in our experiments on spinal dorsal horn neurones than in previous studies on spinal (Davies & Watkins, 1983) and trigeminal neurones (Salt & Hill, 1981, 1983Hill & Salt, 1982). In this series we have not tested PDA on heat-evoked responses which have previously been reported to be PDA resistant (Salt & Hill, 1983).…”
Section: Dorsal Hornmentioning
confidence: 83%
“…The experimental data point to glutamate being strongly implicated at different sites of migraine pathogenesis 35 . Indeed, glutamate excites the TNC neurons when applied locally, and the extracellular levels of glutamate rise following a noxious stimulus along the trigeminal nerve 36,37 . Research findings suggest that the injection of glutamate antagonists in the trigeminocervical complex causes an inhibition of neuronal firing triggered by stimulation of the superior sagittal sinus 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate activates neurons in the trigeminal nucleus caudalis [56] by acting both on ionotropic and metabotropic GluRs [57], and it is involved in signaling from spinothalamic tract and lemniscal pathways and corticothalamic afferents [58]. In vivo studies using micro dialysis and blood flow measurements demonstrated increased levels of glutamate in the TCC during and post stimulation of dural structures and following noxious stimulation along the trigeminal nerve [21,59,60].…”
Section: Glutamate In the Ascending Trigeminovascular Pathwaymentioning
confidence: 99%